2020
DOI: 10.3389/fgene.2019.01310
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Prognostic Dosage-Sensitive Genes in Colorectal Cancer Based on Multi-Omics

Abstract: Several studies have already identified the prognostic markers in colorectal cancer (CRC) based on somatic copy number alteration (SCNA). However, very little information is available regarding their value as a prognostic marker. Gene dosage effect is one important mechanism of copy number and dosage-sensitive genes are more likely to behave like driver genes. In this work, we propose a new pipeline to identify the dosagesensitive prognostic genes in CRC. The RNAseq data, the somatic copy number of CRC from TC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 39 publications
(39 reference statements)
0
8
0
Order By: Relevance
“…Among the positively correlated genes analyzed in the LinkedOmics database, IQCB1 expression was most highly co-altered along with EAF2 expression, followed by ILDR1 and ASTE1, respectively. IQCB1 was found to be associated with poor prognosis in colorectal cancer [24]. Overlapping ASTE1 and ATP2C1 genes in human genome implicate for SPCA1, for affecting cytosolic Ca 2+ -signaling, and in turn perturbing cell division, leading to cell death or to neoplastic transformation [25].…”
Section: Discussionmentioning
confidence: 99%
“…Among the positively correlated genes analyzed in the LinkedOmics database, IQCB1 expression was most highly co-altered along with EAF2 expression, followed by ILDR1 and ASTE1, respectively. IQCB1 was found to be associated with poor prognosis in colorectal cancer [24]. Overlapping ASTE1 and ATP2C1 genes in human genome implicate for SPCA1, for affecting cytosolic Ca 2+ -signaling, and in turn perturbing cell division, leading to cell death or to neoplastic transformation [25].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed that multi-omics analysis, which focuses on biological changes at the genomic, epigenomic and transcriptomic levels, can provide insights for tumorigenesis [36]. For example, Chang et al [37] integrated and analyzed RNA sequence and somatic CNV data to demonstrate dosage-sensitive genes in CRC, which provided a new reference for cancer therapy. In this study, we investigated genes associated with CRC incidence and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the karyopherin family members are dysregulated in cancer, most frequently in the form of elevated expression evident from studies comparing tumour samples to normal adjacent tissues 4,24–28 . Upregulation of karyopherin proteins has been associated with enhanced transport efficiency, which is thought to benefit tumour cells via promoting oncogenic signalling and sustaining the high metabolic and proliferative demands of the cancer phenotype 29 .…”
Section: Nuclear Transport Dysregulation In Cancermentioning
confidence: 99%